Incidence and risk of cardiotoxicity in cancer patients treated with targeted therapies. (September 2017) - Santoni, Matteo; Guerra, Federico; Conti, Alessandro; Lucarelli, Alessandra; Rinaldi, Silvia; Belvederesi, Laura; Capucci, Alessandro; Berardi, Rossana
Highlights: Cardiotoxicity is a serious side effect of molecularly targeted agents. The highest RR of all-grade events was observed with Vandetanib. The highest incidence of high-grade events was shown by anti-VEGFR-TKIs. Patients with thyroid and gastric cancer showed the highest RR of cardiotoxicity. Abstract: Background: Cardiotoxicity is a serious side effect of molecularly targeted agents. The purpose of this study was to evaluate the incidence and Relative Risk (RR) of developing all-grade and high-grade cardiotoxicity in patients with solid tumors receiving targeted agents through a revised meta-analysis of available clinical trials. Methods: The scientific literature regarding cardiotoxicity was extensively analyzed using MEDLINE, PubMed, Embase and Cochrane Central Register of Controlled Trials (CENTRAL). Eligible studies were selected according to PRISMA statement. Summary incidence, RR, and 95% CIs were calculated using random-effects or fixed-effects models based on the heterogeneity of selected studies. Results: Our search yielded a total of 4998 clinical studies; of them, 31 trials were finally considered for this meta-analysis. A total of 28, 538 patients were included; 7995 of these patients had breast cancer (28%), 6151 (22%) prostate cancer and 14, 392 (50%) were treated for other malignancies. The highest RR of high-grade events was observed with Vandetanib (RR = 7.71, 95% CI 1.04–56.99), followed by Ramucirumab (RR = 5.0) and Aflibercept (RR = 4.1). Grouping by drug category, the highest incidence of high-grade cardiotoxicity was shown by anti-VEGFR-TKIs (RR 5.62, 95% CI 1.49–21.24) and anti-VEGF mAbs/VEGF-trap (RR 1.82, 95% CI 1.24–2.69). Grouping by tumor type, the highest incidence of cardiotoxicity was observed in thyroid cancer (8%), followed by gastric cancer (4%). Conclusions: Treatment with targeted agents in cancer patients is correlated with a significant increase in the risk of cardiotoxicity. Frequent clinical monitoring should be emphasized when using these and newer biological agents.